Indoor Aeromycroflora at Institute of Agriculture Library (Visva-Bharati): A Study - Ray, Partha Pratim (Journal of Information and Knowledge, 2017)
Existence of aeromycoflora inside Institute of Agriculture library, Visva-Bharati, Sriniketan India was studied with the help of Burkard Personal one day Volumetric Sampler for eight months from August 2014 to March 2015 with variation of temperature from 11.200C to 33.390C and relative humidity (RH) 51%-86.87%. Ten fungal species namely Drechslera sp.; Aspergilli/penicillin sp.; Bispora sp.; Basidiospore sp.; Ascospore sp.; Nigropora sp.; Pericornia sp.; Fusarium sp.; Cladosporium sp.; Trichornis sp. were identified. Maximum fungal spores were identified in September (8052 spores /m-3 air) and minimum in November (1056 spore /m-3) in air. The findings help take proper preventive measures to control the presence of fungal spores in the air of the library which in turn will save library collections and reduce cause of health hazards to library personnel as well as users.